Analisis Digitalisasi Dalam Fundraishing Pengelola Zakat, Infaq Dan Sedekah (ZIS) Pada Laz Washal - Wulandari, Ayu; Aisyah, Siti (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2022)
Along with the current advances in digitalization of technology which can make every aspect of life change people both to carry out their daily activities and also to charity activities such as paying zakat, infaq, and alms for Muzakki who want to pay their ZIS easily and definitely fast. This research is descriptive qualitative research. Which was carried out to determine the effectiveness of digitization in the ZIS fundraising at Laz Washal. The results of the study show that in terms of ZIS digitalization payments consisting of BSI, Funds, and OVO it has a significant influence on the ZIS digitization payment process at Laz Washal because with that providing ZIS it can be easier and more efficient in making ZIS payments. Thus, people will compete to do ZIS charity at Laz Washal because the digitization of zakat fund collection at LAZ WASHAL is quite effective which can be seen from the sufficient indicators of effectiveness in research.